A contabilidade brasileira no período autoritário militar (1964 - 1985): as principais mudanças na contabilidade nacional e na economia ocorridas neste período - Reis, Igor Sergio dos (2017)
The history of Brazilian accounting is still relatively unexplored, despite the growing publication of articles, dissertations and books in recent years. Through a historical research, the present work sought to examine the main changes occurred in Brazilian accounting in the period of the Military Coup (1964-1985). The need for a greater introduction of accounting in public and business management was associated with the strong economic development that Brazil had, with the expansion of industrialization with its multiplier effect on urban activities. In 1965, due to an apparent lack of credibility of the capital market and lack of income culture of investment in variable income, Law No. 4728/65 was issued, which regulated the Brazilian capital market. In 1964, with the military government of Castelo Branco and the Minister of Finance Bulhões, the Central Bank of the Republic of Brazil was created, which was changed in 1967 to the Central Bank of Brazil, and the treasury loan operation was under its Full responsibility. In 1971 was published the first book of introductory accounting the methodology adopted in the book was based on the book and Finney & Miller, brought by Boucinhas that greatly facilitated the students' understanding. In the late 1960s and early 1970s we had the economic miracle in Costa e Silva's government, during which time the GDP growth rate accelerated from 9.8% per year in 1968 to 14% per year in 1973, linked to an inflation that declined From 25.5% to 15.6% during that period. With the evolution of the accounting profession, the creation of higher accounting courses and the ever increasing needs of the transparency market in the financial statements was favorable to the emergence of independent audits, That in 1957, the Institute of Public Accountants of São Paulo arose. As early as 1968, the Institute of Independent Auditors of Brazil emerged. In 1971, these Institutes merged into the Institute of Independent Auditors of Brazil. In 1976, the Brazilian Corporate Law was adopted, which established the adoption of the US accounting system with some relevant Brazilian contributions. Some national practices, such as monetary correction, brought the following main contributions: the introduction of the revaluation at market value, Introduction of the equity method in the evaluation of investments, creation of the unrealized income reserve, separation of commercial and tax accounts and consolidation of the financial statements of the same group. In the period of the Military Coup, Brazilian accounting presented important development in the areas of public accounting, accounting education and class organizations. There is a significant evolution in the accounting practices of private companies and corporations